Mechanical and thermal properties of corn cob and lavender stem reinforced poly(lactic-acid)-based composites - Lilla Bubenkó; Násfa Németh; Sára Frey; Tamás Molnár; Károly Belina; Orsolya Viktória Semperger (eXPRESS Polymer Letters, 2025)
Biocomposites have recently received more attention because of raising environmental awareness and the drive toward sustainable technologies. The most common biodegradable polymer is poly(lactic acid) (PLA), which has an excellent balance of physical and rheological properties, but there is some limit to its usage. PLA properties can be improved by adding different types of fibers or fillers that come from agricultural waste. In this study, corn cob and lavender stem were used to reinforce PLA without any coupling agent, and the properties of the composites were investigated. The melt flow rate (MFR) values decreased with the corn cob content and increased with the addition of lavender stem. Mechanical tests showed that the tensile and flexural modulus of the composites increased and the strengths decreased with the reinforcement material content. The rigidness of PLA slightly decreased with the addition of fillers. There was no significant effect on the thermal properties. The unremarkable improvement of the reinforcement was due to the lack of appropriate adhesion of the two phases. The structure of the compounds was found to be homogenous on the scanning electron microscopy (SEM) micrographs. The incorporation of corn cob and lavender stem can reduce the production cost of materials.